Entomophilic nematodes, Diploscapter coronatus and Oscheius tipulae from Afghanistan - Falahzadah, Mohammad Hussain; Shokoohi, Ebrahim; Moravej, Gholam Hossein; Mashela, Phatu William; Madadi, Abdul Khalid; Karimi, Javad (Zootaxa, 2021)
Several soil samples from different habitats in Badakhshan province of Afghanistan were collected to isolate and characterize bacteria feeding nematodes. The Galleria mellonella-baiting method was used for the isolation of the Afghan insect-associated nematodes. The nematodes were studied using morphological and morphometric data. The Oscheius specimen was characterized by a longer body (630–820 µm) and shorter pharynx (125–145 µm), whereas other morphological characters were not unusual. The Diploscapter specimen had an annulated cuticle, with lip region width 1.5 times shorter than the stoma, and had separated pharyngeal corpus from the isthmus and vulva located in the middle of the body. The molecular data were derived using three loci; 18S, 28S (D2/D3 segment), and ITS rRNA region, which were utilized to measure the genetic distance. The phylogenetic analysis was conducted to reconstruct the relationship tree. Both morphological and molecular approaches confirmed the identity of nematode isolates as Oscheius tipulae and Diploscapter coronatus. This is the first report of insect-associated nematodes from the soil of Afghanistan. Both species were capable of infecting and killing G. mellonella larvae in less than 96 h.